Does travellers' casual attribution affect pre-recovery emotions and behavioural intentions? A field study of airline travellers in Malaysia. Issue 1 (2nd January 2017) - Nikbin, Davoud; Hyun, Sunghyup Sean
Abstract : This study examines the relationship between airline travellers' casual attribution, pre-recovery emotions, and negative behavioural intentions after a service failure and proposes a model for analysing direct effects of airline travellers' casual attribution of stability (failure frequency) and controllability (the extent to which the airline can control the failure) on negative behavioural intentions as well as its indirect effects through pre-recovery emotions. Data were gathered through a survey of airline travellers who experienced a failure in the past six months. The results indicate that both dimensions of casual attribution influenced pre-recovery emotions and negative behavioural intentions, and that pre-recovery emotions were significantly related to negative behavioural intentions. In addition, the results verify the mediating effect of pre-recovery emotions on the relationship between casual attribution and behavioural intentions. These results have important managerial implications.